Studies on nucleic acid reassociation kinetics: V. Effects of disparity in tracer and driver fragment lengths. - Chamberlin, M E (1978)
Measurements are described of the kinetics of nucleic acid strand pair reassociation where the complementary strands are of different lengths and are present in different concentrations. Rate constants for the reaction of labelled fragments ("tracer") with excess complementary strands ("driver") were determined, both for driver fragment length greater than tracer fragment length and for the reverse case. Second order reactions and pseudo-first order reactions utilizing strand separated drivers and tracers were studied. The nucleic acids which served for this investigation were phiX174 DNA and RNA, plasmid RSF2124 DNA and E. coli DNA. Approximate empirical expressions relating driver and tracer fragment lengths with the observed rate constants were obtained for practical use. In long tracer-short driver reactions the observed rate constant for the tracer reaction increases proportionately with tracer length. In long driver-short tracer reactions the rate of tracer reaction is retarded. The latter result is unexpected and appears to represent a departure from standard interpretations of the renaturation reaction.